Applying Commognitive Theory in Education: A Systematic Literature Review - Zulfah Zulfah; Toto Nusantara; Yusuf Hanafi; Slamet Arifin; Adi Atmoko; Rusdial Marta (AL-ISHLAH: Jurnal Pendidikan, 2026)
The commognitive framework proposed by Sfard has become an influential perspective for examining mathematical thinking as discourse. Although its application in mathematics education has expanded considerably, a comprehensive synthesis of research trends, thematic focus, and bibliometric patterns remains limited. This study systematically reviews the development of commognitive research in education.A systematic literature review following the PRISMA guidelines was conducted. Publications were retrieved from Scopus, Web of Science, ScienceDirect, and Google Scholar using Publish or Perish. After identification, screening, and eligibility assessment, 28 journal articles published between 2018 and 2023 met the inclusion criteria. Data were analyzed through descriptive synthesis and bibliometric visualization using VOSviewer.The findings indicate that Indonesia contributed the largest number of publications on commognitive research, with publication activity peaking in 2022. The reviewed studies primarily involved participants from kindergarten to higher education, including pre-service teachers. Research predominantly explored mathematical discourse, collaborative learning, problem solving, visual mediators, routines, and gender-related issues. Bibliometric analysis revealed interconnected research clusters centered on commognitive framework, discourse, collaborative problem solving, and mathematical communication, reflecting the growing diversification of research themes.The review demonstrates the increasing adoption of the commognitive framework in mathematics education and highlights its diverse applications across educational levels. It also identifies opportunities for future research, particularly in extending commognitive studies beyond mathematics education, employing longitudinal and intervention designs, and strengthening theoretical integration. These findings provide a comprehensive overview of the current state of commognitive research and offer directions for advancing both educational research and classroom practice.